International Legal Aspects of Whale Hunting by Indigenous Legal Communities - Tahalea, Rensy Elma Tahalea; Daties, Dyah Ridhul Airin; Riry, Welly Angela (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Greenland in Denmark, Siberia in Russia, Bequia in the island nation of Saint Vincent and the Grenadines, Alaska in the United States, Canada and the Faroe Islands located in the North Atlantic Ocean are some of the countries that still practice traditional whaling. Unlike Japan, which conducts commercial whaling and uses modern tools. Indonesia is a country that recognizes indigenous peoples and their customary law in the constitution. The Leva Nuang tradition or Lewa tradition is a tradition of the Lamalera people in East Nusa Tenggara Province in carrying out whaling in a traditional way for their own needs. Whales themselves are protected animals in the Convention on International Trade In Endangerad Species of Wild Fauna and Flora (CITES 1973).Purposes of the Research:  The issue discussed in this paper is how international legal instruments regulate whaling and how international law protects the right of indigenous peoples to carry out whaling traditions.Methods of the Research: The research method used is normative juridical, using a concept approach, a statutory approach and a case approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. Analysis of such legal materials uses qualitative analysis techniques.Results of the Research: The results showed that the Convention on International Trade In Endangerad Species of Wild Fauna and Flora (CITES 1973) regulates protected animals, one of which is whales. There is also an international legal instrument governing whaling, the International Convention for the Regulation of Whaling (ICRW 1946). The Government of Indonesia ratified CITES 1973 on December 15, 1978 through Presidential Decree Number 43 of 1978. However, the 1946 ICRW Convention and ILO Convention 169 on Indigenous Peoples have not been ratified by the Indonesian government. Nevertheless, the Indonesian government recognizes and protects the rights of indigenous peoples, including the Leva Nuang tradition or Lewa tradition.